The Effects of Combining Peer Discussion and Isomorphic Problems (PD-IPs) on High School Students' Academic Achievements - Tolga Gok (Universitas Pendidikan Indonesia, 2023)
The study investigated the effects of a combination of Peer Discussion and Isomorphic Problems (PD-IPs) on high school students' graph understanding and conceptual learning. The study was conducted on kinematics and Newton’s Laws of Motion with 67 high school students from two groups. The experimental group (EG) consisted of 34 students, while the control group (CG) combined with 33 students. The students in EG were taught using the PD-IPs approach, while those in CG were taught using the traditional method. The research data were collected using the Force Motion Achievement Test (FMAT), which was composed by selecting multiple-choice questions from some standardized tests (Force Concept Inventory, Mechanic Baseline Test, Test of Understanding Graphs in Kinematics). The FMAT includes 25 multiple-choice questions. 11 were related to graph understanding, and the rest were related to conceptual learning. The research showed that the PD-IPs approach had a more positive effect on students' understanding of graphs and conceptual learning than the traditional teaching method. The findings indicate that implementing the PD-IPs approach requires minimal effort while demonstrating the potential to evaluate and improve high school student's academic performance in physics education.